2013
DOI: 10.3390/molecules180910599
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Antimicrobial and Antiprotozoal Evaluation of Garcinia Mangostana Pericarp and α-Mangostin, Its Major Xanthone Derivative

Abstract: Five xanthone derivatives and one flavanol were isolated from the dichloromethane extract of Garcinia mangostana. Dichloromethane, ethyl acetate extract and the major xanthone (α-mangostin) were evaluated in vitro against erythrocytic schizonts of Plasmodium falciparum, intracellular amastigotes of Leishmania infantum and Trypanosoma cruzi and free trypomastigotes of T. brucei. The major constituent α-mangostin was also checked for antimicrobial potential against Candida albicans, Escherichia coli, Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 28 publications
1
56
1
2
Order By: Relevance
“…The 1 H-NMR spectrum of compound (2) looked very similar to that of ɑ-mangostin (1), except that instead of having one methoxyl group it had two at (d, ppm, multplicity) 56.30 (3H, s) and 61.4 (3H, s). Other (Table 1 and Table 2) it was concluded that compound (2) was identified as known β-mangostin [13]. ) at m/z 395.495, this compound was identified as known compound gartanin [12].…”
Section: Resultsmentioning
confidence: 95%
“…The 1 H-NMR spectrum of compound (2) looked very similar to that of ɑ-mangostin (1), except that instead of having one methoxyl group it had two at (d, ppm, multplicity) 56.30 (3H, s) and 61.4 (3H, s). Other (Table 1 and Table 2) it was concluded that compound (2) was identified as known β-mangostin [13]. ) at m/z 395.495, this compound was identified as known compound gartanin [12].…”
Section: Resultsmentioning
confidence: 95%
“…Swertia species have also been investigated for the presence of essential elements [105][106][107]. Xanthones have been reported to display hepatoprotective, antimicrobial, anticarcinogenic, antileprosy, antioxidant, anticholinergic, mutagenicity [108,109], and radioprotective effect [110], immunomodulatory effect [111], antibone resorption [112], and antiparasitic effects [113], neuraminidase inhibitory [114], antimalarial [115], anticomplement [116], antifungal and algicidal [117], and anti-HIV activity [118], and cardioprotective, antitumoral, antibacterial, antidiabetes, antihyperlipidemic, antiatherogenic, immunomodulator, anti-inflammatory, antiulcer, antiviral, antifungal [119], antidiabetic, hypolipidemic [120], analgesic, antiasthmatic, antihistaminic, antiamoebic, diuretic, antidiarrheal, larvicidal, ovicidal, antiprotozoal, antileptospiral, anti-TMV, and anticancer activities [121][122][123][124]. Xanthones from S. mussotii were evaluated for their anti-hepatitis B virus activity on HepG 2.2.15 cells line; they exhibited significant activity inhibiting hepatitis B virus DNA replication with IC 50 values from 0.01 mM to 0.13 mM [125].…”
Section: Biological Activities Of Xanthonesmentioning
confidence: 99%
“…The effectiveness of alpha-mangostin against E. coli bacteria uropatogen was evaluated with broth dilution method using a series of specific levels of alphamangostin in broth or liquid media (MHB) (Figure 1). The level range was as described by Al Massarani et al (2013), who reported that alpha activity mangostin dimetilsulfoxide diluted with dimethylsulfoxide (DMSO) for E. coli in the form of IC50 values of v> 200 µM (equivalent to 82.09 mg/mL). In addition to the use of a serial level, one tube without alpha mangostin (positive control) was used as a control of bacterial growth and a negative control tube (sterile bacterial media and alfa mangostin without bacteria) as a sterility control.…”
Section: A Population and Sample Researchmentioning
confidence: 99%
“…Other studies on antibacterial activity of mangostin was coducted by Zou et al (2013) stating that the test on the effect of mangostin against Pseudomonas aeruginosa and Klebsiella pneumoniae resulted in MIC of 40-50 µg/mL. The studies on effect of α-mangostin against several bacteria including Escherichia coli have also been carried out by Al Massarani et al in 2013 resulting in E. coli IC 50 >200 µg/mL.…”
Section: Statistic Analysismentioning
confidence: 99%
See 1 more Smart Citation